Country versus Region Effects in International Stock Returns - Robin Brooks; Marco Del Negro (Federal Reserve Bank of Atlanta, 2003)
An empirical regularity in the portfolio diversification literature is the importance of country effects in explaining international return variation. We develop a new decomposition that disaggregates these country effects into region effects and within-region country effects. We find that half the return variation typically attributed to country effects is actually due to region effects, a result robust across developed and emerging markets, with the remaining variation explained by within-region country effects. For the average investor, this means that diversifying across countries within Europe, for example, delivers half the risk reduction possible from diversifying across regions globally.
Keywords: 330; Financial markets; Risk